Association of elevated blood serum high-sensitivity C-reactive protein levels and body composition with chronic kidney disease: A population-based study in Taiwan. Issue 36 (September 2018) - Tsai, Yi-Wen; Chan, Yi-Ling; Chen, Yi-Chuan; Cheng, Yiu-Hua; Chang, Shy-Shin
Abstract : Abstract: Chronic kidney disease (CKD) is a risk factor for cardiovascular diseases and is associated with an increase in all-cause mortality. Studies regarding association among various body compositions in different inflamed states and the risk of CKD were rare. We aimed to evaluate the relationship among body composition, high-sensitivity C-reactive protein (hsCRP) level, and the risk of CKD. This was a retrospective cross-sectional study using annual health examination data from 2 medical centers in northern and southern Taiwan between January and December 2015. We performed a variance analysis of the estimated glomerular filtration rate (eGFR) distribution in groups based on hsCRP and body fat percentage (BFP), and a multivariate logistic regression model was used to assess the relationship among BFP, hsCRP levels, and CKD. A total of 10, 267 subjects aged ≥18 years undergoing health examination were analyzed. In our study, overweight/obese patients were associated with increased risk of CKD. Nevertheless, in subjects with elevated hsCRP level, overweight/obese group with a higher BFP had a lower risk of CKD as compared with overweight/obese with normal BFP group (for BMI ≧ 23 kg/m 2, high BFP/high hsCRP: odds ratio [OR] for CKD 1.86, 95% confidence interval [CI] = 1.10–3.17, P = .02; normal BFP/high hsCRP group: OR 2.32, 95% CI = 1.23–4.37, P = .01) after adjusting for various confounders. Our findings suggest that various body compositions in different inflamed states may interfere with the risk of CKD. These results provide an important method for the early detection of impaired renal function by identifying various body compositions and inflammation states to detect CKD at an earlier stage. Abstract : Supplemental Digital Content is available in the text